A Study of Empirical Use of Proton Pump Inhibitors in Indoor Patients - Javed Chaudhry, Asma Inam, Khadija Javed, Abdullah Javed, Gulpash Saghir, Najma Shoaib (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Proton pump inhibitors are amongst most widely used gastric protectants due to their effectiveness. However, there are concerns about their over utilization, patient safety and socioeconomic burden. Aim: To evaluate empirical use, risks and hazards associated with over- usage of Proton pump inhibitors (PPIs). Methodology: A descriptive cross-sectional study was conducted at a tertiary care hospital in Lahore from July to August 2021. Seventy five patients were randomly picked up from indoor wards of the hospital. Patient’s demographic data and frequency of PPIs usage was recorded. Route of administration, adverse effects and indications of proton pump inhibitors were also noted in percentages. Results: All patients were prescribed PPIs on their admission day. Among them, two patients were concomitantly taking H2 Receptor Blockers. Seventy eight (78 %) users were administered PPIs through intravenous route, while rest were given once daily oral formulation. Fourty two (42) % of patients were not prescribed PPIs according to AGA criteria. Moreover, 12% of our sample population suffered from different adverse effects like diarrhea, abdominal pain, bone pain and headache. The results of our study clearly indicated frequent use of PPIs in indoor patients as a prophylaxis of SRMD. Conclusion: Keeping in view the incorrect use of antiacids and their adverse effects including increased risk of enteric and hospital acquired infection, unnecessary use of PPIs in admitted patients should be monitored regularly. MeSH words: PPIs, SRMD, NSAIDs, AG